9H-Carbazole-1-carboxamides as potent and selective JAK2 inhibitors. Issue 14 (15th July 2015) - Zimmermann, Kurt; Sang, Xiaopeng; Mastalerz, Harold A.; Johnson, Walter L.; Zhang, Guifen; Liu, Qingjie; Batt, Douglas; Lombardo, Louis J.; Vyas, Dinesh; Trainor, George L.; Tokarski, John S.; Lorenzi, Matthew V.; et al.
Graphical abstract: The discovery, synthesis, and characterization of 9 H -carbazole-1-carboxamides as potent and selective ATP-competitive inhibitors of Janus kinase 2 (JAK2) are discussed. Abstract: The discovery, synthesis, and characterization of 9 H -carbazole-1-carboxamides as potent and selective ATP-competitive inhibitors of Janus kinase 2 (JAK2) are discussed. Optimization for JAK family selectivity led to compounds14 and21, with greater than 45-fold selectivity for JAK2 over all other members of the JAK kinase family.